DYNAMIC ALLOCATION OF SPECTRUM IN HYBRID ACCESS COGNITIVE FEMTOCELL NETWORKS WITH PRACTICAL SPECTRUM SENSING - et al., Ch.V.M.S.N.Pavan Kumar (International Journal of Advanced Science and Technology, 2019)
The demand for the data increasing progressively in the next generation cellular networks. To satisfy the demands, the operators are moving towards the data minded cellular technologies like 5G. As the frequency of operation increases, the pathlosses also becoming more and more, the service for the indoor user is becoming a serious question. To address this problem, femtocell is nominated as a candidate in the literature. Femtocells operates in the same frequencies with the macrocell, because of this co-channel interference between macro-femto (Cross-tier) and femto-femto (Co-tier) is a serious problem. Cognitve Radio (CR) technology is the one of the promising one to access the unused spectrum bands. This work deals with the incorporation of CR technology with hybrid access femtocell networks. In this paper a dynamic resource allocation technique is proposed in hybrid access cognitive femtocell networks with perfect spectrum sensing and fairness. The results are showing that this technique yields better throughput, fairness among the users.